2021
DOI: 10.3389/fgene.2021.599863
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Aids the Diagnosis of Fetal Skeletal Dysplasia

Abstract: Skeletal dysplasia is a complex group of bone and cartilage disorders with strong clinical and genetic heterogeneity. Several types have prenatal phenotypes, and it is difficult to make a molecular diagnosis rapidly. In this study, the genetic cause of 16 Chinese fetuses with skeletal dysplasia were analyzed, and 12 cases yielded positive results including one deletion in DMD gene detected by SNP-array and 14 variants in other 6 genes detected by whole exome sequencing (WES). In addition, somatic mosaicism was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
10
3
Order By: Relevance
“…Prenatal ES identified well-described genetic causes in 38 out of 94 cases (40.4%), and VUS in 5 cases, rendering a total diagnostic yield of 45.74%. Compared with our findings, three recent cohort studies reported a significantly higher diagnostic rate by prenatal ES, which was 80% (12 out of 15), 85% (11 out of 13), and 70% (21 out of 30), respectively (Liu et al, 2019;Peng et al, 2021;Tang et al, 2021). Many aspects could affect the detection rate of ES, such as the selected criteria of the study, the number of cases, proband-only or trio ES, and so on (Tang et al, 2021).…”
Section: Follow-up Assessmentscontrasting
confidence: 81%
See 2 more Smart Citations
“…Prenatal ES identified well-described genetic causes in 38 out of 94 cases (40.4%), and VUS in 5 cases, rendering a total diagnostic yield of 45.74%. Compared with our findings, three recent cohort studies reported a significantly higher diagnostic rate by prenatal ES, which was 80% (12 out of 15), 85% (11 out of 13), and 70% (21 out of 30), respectively (Liu et al, 2019;Peng et al, 2021;Tang et al, 2021). Many aspects could affect the detection rate of ES, such as the selected criteria of the study, the number of cases, proband-only or trio ES, and so on (Tang et al, 2021).…”
Section: Follow-up Assessmentscontrasting
confidence: 81%
“…In the last decade, next-generation sequencing (NGS) has revolutionized the genetic testing of diseases with high genetic and allelic heterogeneity, such as skeletal dysplasias, allowing hundreds of genes to be screened simultaneously. Based on the statements released by the International Society for Prenatal Diagnosis (ISPD), the Society for Maternal Fetal Medicine (SMFM), the Perinatal Quality Foundation (PQF), and the American College of Medical Genetics and Genomics (ACMG), NGS can be used with ultrasound anomalies when standard diagnostic genetic testing, such as CMA, failed to yield a definitive diagnosis (Lord et al, 2019;Tang et al, 2021). In addition, SLBs are mainly attributed to monogenic disorders, such as skeletal dysplasias (Mortier et al, 2019), and therefore NGS may be of importance in their prenatal evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quantitative analysis, 40 articles [121, were secondarily excluded. Of these, three papers focused on fetal demises or stillbirths [256][257][258], three papers focused on information postmortem [242,250,254], three were case reports [238,246,252], five focused on a single specific phenotype [240,241,248,261,274], three presented inhomogeneity in inclusion criteria and chromosomal anomalies/CNV assessment [239,251,262], six included both fetuses and postnatal cases [244,249,253,259,260,269], three focused on candidate genes [243,247,263], three focused on recurrent phenotypes or previously described cohorts [245,255,272], five were excluded for the lack of inclusion or eligibility criteria [264,265,268,271,276], two were excluded for the higher a priori risk for consanguinity and recurrence [266,270], one because parents were tested for recessive disorders [267], two because they focused on gene panels [273,275], and one due to the postnatal diagnosis [121].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…The spectrum of the diagnoses that do not belong to the FDH is quite similar to that previously reported in literature. 20,[31][32][33][34] Some skeletal dysplasias, such as achondroplasia, are often diagnosed later in pregnancy. 35 Therefore, in these skeletal dysplasias, prenatal diagnostic methods are rarely of use in the management of pregnancy.…”
Section: Casementioning
confidence: 99%